PENYULUHAN DAN PEMBINAAN MANFAAT DAN BUDIDAYA TANAMAN SURGAWI - Nazwirman Nazwirman; Juniarti Juniarti; Zainal Zawir Simon (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2020)
This activity aims to provide knowledge about the various benefits of heavenly plants and planting patterns of date (Kurma), tin and bidara cultivation for cleaners in the Banjar Wijaya housing complex in Tangerang City. The activity was given in the form of counseling and coaching about the benefits and ways of cultivating heavenly plants. As a result, as many as 12 participants increased their knowledge significantly both about the method of utilization and cultivation. This activity was at once a socialization of the theory and practice of plant benefits contained in the Qur'an and the Sunnah of the prophet with a sharing and accompaniment approach.